2018
DOI: 10.1111/ctr.13244
|View full text |Cite
|
Sign up to set email alerts
|

Preformed donor‐specific antibodies do not affect the 1‐year allograft survival in living donor liver transplantation

Abstract: The effect of preformed donor-specific antibodies (DSAs) on liver transplantation (LT) remains unclear, especially in the field of living donor LT (LDLT). Herein, we evaluated the prevalence of preformed DSAs and their effect on graft outcome in LDLT in the first year following surgery. Using the Luminex Single Antigen assay, we analyzed the preoperative sera of 61 adult LDLT recipients between 2014 and 2015. Clinical outcomes and pathologic findings including complement component 4d (C4d) expression in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Few studies have evaluated anti‐HLA antibodies, including DSAs, using Luminex examination of LDLT recipients in Asia . There has been only one study at Kyoto University (Kyoto, Japan), which reported using pretransplant sera from 18 of 21 recipients whose preoperative CDC tests were positive .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have evaluated anti‐HLA antibodies, including DSAs, using Luminex examination of LDLT recipients in Asia . There has been only one study at Kyoto University (Kyoto, Japan), which reported using pretransplant sera from 18 of 21 recipients whose preoperative CDC tests were positive .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al . showed that preformed DSAs were not related to graft or patient survival . In their study, irrespective of the presence of preformed DSAs, the patient survival rate was 100% and the postoperative acute cellular rejection rate was very low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In kidney transplantation, the presence of a positive complement-dependent cytotoxic (CDC) crossmatch and a high titre of donor-specific antibodies (DSAs) may be considered a contraindication for transplantation, due to the risk of hyper-acute rejection and subsequent graft loss. In contrast, the presence of preformed DSAs in liver transplant recipients has a much less deleterious clinical effect, with no difference observed in 12-month allograft outcomes in sensitised liver transplant recipients [1]. Simultaneous liver-kidney transplantation (SLKT) may abrogate the risk to the kidney, as illustrated by previous case reports of successful SLKT among highly sensitised patients [2].…”
Section: Introductionmentioning
confidence: 99%